CONSTRUCTING NATIONAL ENVIRONMENTAL LEGAL POLICIES IN RESPONSE TO THE CHALLENGES OF A WORLD FREE MARKET IN THE AGE OF GLOBALIZATION - Akbar Taufik Amrullah; Farida Nur Hidayah (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This study's objective is to investigate the policy of national environmental law politics in light of the problems posed by the global free market in the era of globalization. This study employs a legal normative research methodology with a statute approach. The study's findings indicate that environmental protection and management based on environmental legal standards necessitates a balance between economic interests, the maintenance of environmental functions, and social conditions. All this time, the two objects seemed to be divided from each other. Government and the corporate sector are perceived as entities that place commercial interests above environmental protection. Economic development alone has been ineffective in reducing poverty, averting social conflicts caused by unequal access to natural resources, and increasing the rate of environmental degradation. A legal settlement that can be used as a guide for environmental law enforcement officials against environmental laws and regulations that contain criminal penalties that are not in harmony with the provisions of Law No. 32 of 2009 as one of the legal adages: (i) lex specialis derogat legi generali, (ii) lex superior gerogat legi inferiori, and (iii) lex posterior derogat legi anteriori.